Plantas ornamentais em quintais urbanos de Rio Branco, Brasil - Siviero, Amauri; Delunardo, Thiago Andrés; Haverroth, Moacir; Oliveira, Luis Cláudio de; Roman, André Luis Cote [UNESP]; Mendonça, Ângela Maria da Silva (MCTI/Museu Paraense Emílio Goeldi, 2014)
Ornamental plants are important in the culture and welfare of city dwellers in the Amazon. This study aimed to perform a characterization of species of ornamental use in urban backyards of Rio Branco and relation with social aspects of the respondents. Semi-structured interviews featuring ornamental species along with analysis of social aspects of urban respondents of the 132 backyards in Rio Branco, Acre, Amazon between 2009 and 2011. Selected for this study were neighborhoods Aeroporto Velho, Placas and Novo Horizonte, located on the periphery of the municipality. Were detected 140 ornamental species belonging to 49 different botanical families, especially Euphorbiaceae (7%), Arecaceae (6.4%) and Araceae (5%). Ornamental species recorded, 57.5% are exotic, 16% have medicinal use and 44% herbaceous. Regression analysis of data across the diversity of species, area and social parameters of the respondents was not significant. The cultivation of ornamental plants in urban backyards Rio Branco assists in the ambience of the residence, landscape improvement, generates welfare for residents at leisure space beyond the conservation of genetic resources.

As plantas ornamentais são importantes na cultura e no bem estar dos moradores das cidades na Amazônia. Este trabalho teve como objetivo caracterizar as espécies vegetais de uso ornamental em quintais urbanos de Rio Branco, Acre, e a relação com aspectos sociais. Foram realizadas entrevistas semiestruturadas, abrangendo 132 quintais urbanos, entre 2009 e 2011. Os bairros selecionados para este estudo foram Aeroporto Velho, Placas e Conjunto Novo Horizonte, situados na periferia do município. Foram catalogadas 140 espécies ornamentais, pertencentes a 49 famílias botânicas, com destaque para Euphorbiaceae (7%), Arecaceae (6,4%) e Araceae (5%). Entre as espécies ornamentais registradas, 57,5% são exóticas, 16% apresentam uso medicinal e 44% são herbáceas. A análise de regressão dos dados entre a diversidade de espécies, a área e os parâmetros sociais dos entrevistados não mostrou significância. O cultivo de plantas ornamentais em quintais urbanos de Rio Branco auxilia na ambiência da residência e melhoria da paisagem, gera bem estar aos moradores pelo espaço de lazer e contribui para a conservação de recursos genéticos.
Ornamental plants in urban homegardens of Rio Branco, Brazil
Keywords: Ornamentals plants; Urban homegardens; Amazon; Ethnobotany; Plantas ornamentais; Quintais urbanos; Amazônia; Etnobotânica